2022
DOI: 10.1177/03635465221118582
|View full text |Cite
|
Sign up to set email alerts
|

Patient Acceptable Symptom State, Minimal Clinically Important Difference, and Substantial Clinical Benefit After Arthroscopic Superior Capsular Reconstruction

Abstract: Background: Patient Acceptable Symptom State (PASS), minimal clinically important difference (MCID), and substantial clinical benefit (SCB) have rarely been assessed after arthroscopic superior capsular reconstruction (ASCR) with fascia lata autograft. Purpose: (1) To investigate PASS, MCID, and SCB values for pain visual analog scale (pVAS), American Shoulder and Elbow Surgeons (ASES) score, Constant score, and Single Assessment Numeric Evaluation (SANE) after ASCR with fascia lata autograft, (2) to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 52 publications
2
22
0
Order By: Relevance
“…The current cohort revealed that a higher preoperative VAS score favoured earlier MCID achievement but higher preoperative ASES and SANE scores contributed to delayed MCID achievement, demonstrating the previously reported important roles of preoperative functional conditions in MCID achievement [8,28]. Yeom et al found lower preoperative scores to generate significantly higher odds ratios in the postoperative MCID and substantial clinical benefit, suggesting a higher possibility of achieving MCID and substantial clinical benefit after arthroscopic superior capsular reconstruction [28]. Similarly, Evuarherhe et al found a lower preoperative ASES score to be predictive of the achievement of MCID and substantial clinical benefit [8].…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…The current cohort revealed that a higher preoperative VAS score favoured earlier MCID achievement but higher preoperative ASES and SANE scores contributed to delayed MCID achievement, demonstrating the previously reported important roles of preoperative functional conditions in MCID achievement [8,28]. Yeom et al found lower preoperative scores to generate significantly higher odds ratios in the postoperative MCID and substantial clinical benefit, suggesting a higher possibility of achieving MCID and substantial clinical benefit after arthroscopic superior capsular reconstruction [28]. Similarly, Evuarherhe et al found a lower preoperative ASES score to be predictive of the achievement of MCID and substantial clinical benefit [8].…”
Section: Discussionsupporting
confidence: 71%
“…A shoulder MRI was performed with a 3T machine (Achieva; Philips Healthcare) before SCR. On MRI, the Goutallier classification was used to assess fatty infiltration of the RC muscles [20], and the Patte classification was used to assess RC retraction [28]. All imaging evaluation was performed by a fellowship‐trained shoulder surgeon (H.B.)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the variables have been shown to have an effect on the surgical results of aRCR and aSCR. 21,24,46,48,51,54…”
Section: Methodsmentioning
confidence: 99%